Flap‐site Fragment Restores Back Wild‐type Behaviour in Resistant Form of HIV Protease. Issue 12 (26th July 2018) - Luchi, Adriano; Angelina, Emilio; Bogado, Lucrecia; Forli, Stefano; Olson, Arthur; Peruchena, Nélida
Abstract: HIV‐1 protease (HIV‐PR) performs a vital step in the virus life cycle which makes it an excellent target for drug therapy. However, due to the error‐prone of HIV reverse transcriptase, mutations in HIV‐PR often occur, inducing drug‐resistance to inhibitors. Some HIV‐PR mutations can make the flaps of the enzyme more flexible thus increasing the flaps opening rate and inhibitor releasing. It has been shown that by targeting novel binding sites on HIV‐PR with small molecules, it is possible to alter the equilibrium of flap conformational states. A previous fragment‐based crystallographic screen have found two novel binding sites for small fragments in the inhibited, closed form of HIV‐PR, termed flap and exo sites. While these experiments were performed in wild type HIV‐PR, it still remains to be proven whether these small fragments can stabilize the closed conformation of flaps in resistant forms of the enzyme. Here we performed Molecular Dynamics simulations of wild type and mutant form of HIV‐PR bound to inhibitor TL‐3. Simulations show that on going from wild type to 6X mutant the equilibrium shifts from closed to semi‐open conformation of flaps. However, when fragment Br6 is placed at flap site of mutant form, the enzyme is restored back to closed conformation. This finding supports the hypothesis that allosteric inhibitors, together with active site inhibitors could increase the number of point mutations necessary for appreciable clinical resistance to AIDS therapy. Abstract :